(untitled) (Prostor, 2023)
Often quoted as the queen of an oasian region, namely the Zibans, Biskra, a southern Algerian city, was a famous winter station renowned for its tourist character during the French colonization (1830-1962). This stimulated the colonizing authorities to build several hospitality buildings, the largest of which were edified using imported constructive techniques, but with local constructive materials and several local spatial organizations and regional decorative motives. In continuation of previous research work carried out by the first author of this article, this study aims to analyse and classify Biskra’s main hotels to draw up an architectural typology using Philippe Panerai’s method. As a result, four models were identified within the corpus of the study, including seven (7) hotels. Its findings could be considered as strong, helpful support for future research in the field of architectural heritage, regardless of building typology, as well as an appropriate database for the heritage buildings’ practical preservation. Moreover, such research work should inform about other various underrated and misjudged heritage buildings dating from the colonial era in Algeria.